Larvicidal Effect of Vorticella microstoma (Ehrenberg, 1830) on Mosquito Larvae, and Morphological Changes under Induced Environmental Conditions - Achini Koshila Ranasinghe; L. D. Amarasinghe (Journal of Parasitology Research)
Development of microbiota assemblage usually occurs in all most all domestic and peridomestic mosquito breeding habitats. There may be parasitic, epibiont, pathogenic, or even predatory species among this biota, and to investigate their potential against the mosquito population is worth studying. This may contribute to formulating environmentally agreeable approaches in controlling mosquitoes which is a current need. Vorticella spp. is a peritrich ciliate, and its trophont stage has become epibiont to certain biota. Further, their existence in seasonal water bodies that dry off during drought in tropical weather conditions is not known. Therefore, the potential of the larvicidal effect of Vorticella microstoma on different species of mosquito larvae was studied. We found that V. microstoma causes the 100% death of the third instar larvae of Culex tritaeniorhynchus (Giles, 1901) within 48 h of exposure. In contrast to that, this species did not cause any mortality to Aedes albopictus (Skuse, 1894) and Aedes aegypti (Linnaeus in Hasselquist, 1762) mosquito larvae in repeated trials. The dynamics of polymorphism of V. microstoma was studied under induced environmental conditions. V. microstoma remained as trophont stage throughout at room temperature (25±2°C). When the temperature was reduced to 6°C, V. microstoma settled in the cyst stage. Evidently, V. microstoma is a good biocontrol agent of Culex species mosquito larvae, and they able to overcome drought periods in cyst forms. The findings of this study would be considered as the first step for a new avenue to work on environmentally agreeable manner in reducing the Culex spp. mosquito populations.